ANALISIS FAKTOR YANG MEMPENGARUHI SISWA MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI (Survey Pada Siswa Kelas XII SMK Negeri 3 Kuningan) - Novi Satria Pradja; Suwardi Suwardi (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2018)
AbstractBackground of this research is less motivation continue education to college on students class XII in SMK Negeri 3 Kuningan, Brebes, Central Java. it shows the data graduate students which are show that graduate in SMK Negeri 3 Kuningan only 17% to continue college. the aim this research is knows the effect between variable X1 (Condition of parent’s economic social) and vriable X2 (achievement   of students learning) on variable Y (motivation continue education to college)Method used in this research is survey method and type and type this research used is correlation research.  population in this research is student in class XII total 320 students with total of sample are 165 sample. collecting data technique used is questionnaire with likert scale 5 option. data analysis uses path analysis with help IBM SPSS stastistic 20 program.The base of collecting data are as follows: 1) there is a positive influence and significant condition of parent’s social economic to achievement of students learning. 2) there are a positive influence and significant  condition of parent’s social economic to college. 3) there are a positive influence and significant  achievment of students learning to continue college.Suggestion for students so not only rely on cost from their parents to buy study facility and cost school to support study achievement and improve  motivation to continue college . then, to next research because this research limited to condition variable of parent’s social economic and achievement students learning which influence a motivation to continue college. so, expected  to analyzing about motivation to continue college seen from others factor like are intellectual intelligence, interest to learn, etc. Key words: condition of parent’s social economic, achievement of students learning, and motivation to continue college